Photolytic degradation of the β-blocker nebivolol in aqueous solution. (1st June 2017) - Salma, Alaa; Lutze, Holger V.; Schmidt, Torsten C.; Tuerk, Jochen
Abstract: Nebivolol (NEB) is one of the top-sold prescription drugs belonging to the third generation of beta-blockers. However, so far, occurrence data in the environment are lacking. Within this study NEB has been found for the first time in effluent samples of wastewater treatment plants in Germany with an average concentration of 13 ng L −1 . Its photodegradation behavior in the environment and in technical processes is largely unknown. To fill this gap, three different UV treatment procedures (UV-C at 254 nm, UV-B at 312 nm and UV-A at 365 nm) were investigated in three different matrices: pure water, pure water in presence of the hydroxyl radical (OH) scavenger tert. -butanol and real wastewater. No elimination was observed during UV-A treatment. In contrast, NEB degradation during UV-B and UV-C treatment followed pseudo first order reaction kinetics, with highest removal rate during UV-C treatment in pure water (k = 7.8 × 10 −4 s −1 ). The rate constant for UV-C irradiation decreased to 2.9 × 10 −4 s −1 in the presence of the OH scavenger and in the presence of the wastewater matrix. The rate constant for the UV-B lamp was 4.4 × 10 −4 s −1, Three transformation products were identified after UV-B and UV-C photolytic degradation using high resolution mass spectrometry. The main photoreaction is the substitution of the fluorine atoms of NEB by hydroxyl groups. A photolytic cleavage of the CF bond can be excluded as the high bond dissociation energy of aromatic CF bonds (525 kJ mol −1 ), exceeds the energy of electromagnetic radiation applied in the present study (≥254 nm, i.e., max. 471 kJ E −1 ). The quantum yields for NEB degradation for the UV-C lamp achieved in pure water, the OH scavenged system and wastewater matrix were Φ deg = 0.53, 0.19 and 0.22, respectively. For UV-B Φ deg was 0.023 ± 0.003, noticeable differences in quantum yield were not found. The photooxidation involves reactive oxygen species such as superoxide and singlet oxygen. These oxidative species may be formed upon reaction of photo-excited NEB with oxygen. Graphical abstract: Highlights: Detection of up to 31 ng L −1 Nebivolol in German wastewater treatment plant effluents. Investigation of NEB photodegradation in pure water and wastewater. Structure elucidation of three new transformation products by HRMS. Proposal of a photodegradation mechanism with explanation of the obtained TPs.